The relation between maternal serum leptin level and glucose in gestational diabetes and in normal pregnancy - Mustafa Al-Ahmad, Basma Ezzat; Sulaiman, Waleed Raouf; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Hajjaj, Muna (Academic Information Press, 2012)
Leptin , a cytokine secreted by adipocytes was suggested to play an important role in many endocrine regulations, including adiposity , puberty and fertility. Leptin levels are strongly correlated with body mass index (BMI) and total fat mass. The role of leptin during pregnancy especially in maternal-fetal metabolism and intrauterine growth remain unclear .Therefore, the measurement of leptin hormone during pregnancy may eventually be helpful in predicting patient risk of developing gestational diabetes .this study is done to monitor serum leptin changes in pregnant women’s associated with Gestational diabetes (GDM) and to compare them with normal pregnancy with particular emphasis on fasting blood glucose (FBG) concentration.it is a prospective randomized double blind study. 42 pregnant women in 2nd & 3rd trimester Participated in this study, Obesity, hypertension and previous history of diabetes were used as exclusion criteria. The base line level of serum leptin was 6.9±1.8 ng/ml in healthy non-pregnant women’s, whereas the base line values of serum leptin was 1.83 ±1.17 ng/ml and 1.86±1.10 ng/ml for group 1 and group 2 respectively, this difference is statistically significant. However, the values of leptin between group 1 and group 2 were similar. In group 1, serum leptin concentration 1.83±1.17 ng/ml was negatively correlated with FBG 172.3±41.3 mg/dl.whereas in group 2 the negative correlation between the concentration of serum leptin and FBG was very weak.GDM is associated with a significant reduction in the level of serum leptin. This is may be related to an altered relationship between energy requirement, and leptin metabolism in GDM